2004
DOI: 10.1161/01.hyp.0000119189.82659.52
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Protein Zyxin Is a Mechanosensitive Modulator of Gene Expression in Vascular Smooth Muscle Cells

Abstract: Abstract-Excessive deformation of vascular smooth muscle cells (SMCs) caused by a prolonged increase in blood pressure (eg, in hypertension) results in an adaptive remodeling of the vessel wall that is characterized by SMC hypertrophy or hyperplasia and contributes to fixation of the increase in blood pressure. The onset of this process is characterized by a unique change in gene expression in the SMC. However, thus far, no transcription factor has been identified that specifically mediates mechanosensitive ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 19 publications
4
90
0
2
Order By: Relevance
“…Silencing of zyxin in HeLa cells resulted in significantly reduced actin stress fibres (Griffith et al, 2005), whereas under cyclic stretch zyxin only dissociated from focal contacts and accumulated in the nucleus, without affecting vinculin or actin filaments (Cattaruzza et al, 2004). Recent data show that in genetically zyxin-deficient fibroblasts, focal adhesions are depleted from Mena and VASP, and that cells lacking zyxin display deficits in actin cytoskeleton remodelling (Hoffman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of zyxin in HeLa cells resulted in significantly reduced actin stress fibres (Griffith et al, 2005), whereas under cyclic stretch zyxin only dissociated from focal contacts and accumulated in the nucleus, without affecting vinculin or actin filaments (Cattaruzza et al, 2004). Recent data show that in genetically zyxin-deficient fibroblasts, focal adhesions are depleted from Mena and VASP, and that cells lacking zyxin display deficits in actin cytoskeleton remodelling (Hoffman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cyclic stretching the substratum results in the translocation of zyxin from FAs to nuclei in smooth muscle cells. 46 This translocation of zyxin may be involved in the mechano-induced gene transcription, because zyxin family proteins have been suggested to mediate transcription process through their interaction with transcription factors. 25 In this review, we discuss the role of zyxin as a key element of mechanotransducing systems at cell adhesive structures: force-dependent recruitment of zyxin to FAs, SFs and AJs would facilitate actin polymerization at these structures.…”
Section: Mini-reviewmentioning
confidence: 99%
“…Several proteins, including zyxin and vasodilator-stimulated phosphoprotein (VASP), are known to localize to a variable extent at focal adhesions (Crawford et al, 1992;Rottner et al, 2001), or to shuttle between focal adhesions and the nucleus (Nix and Beckerle, 1997;Aplin and Juliano, 2001). Recent studies further indicated that mechanical stimulation can induce the change in distribution of zyxin from focal adhesions to either actin stress fibers in cultured fibroblasts (Yoshigi et al, 2005), or the nucleus of vascular smooth muscle cells (Cattaruzza et al, 2004). The latter may be related to the suspected ability of zyxin to regulate gene expression (Degenhardt and Silverstein, 2001).…”
Section: Introductionmentioning
confidence: 99%